Perspectives on research assessment in architecture, music and the arts : discussing doctorateness - Nilsson, Fredrik, 1965-; Dunin-Woyseth, Halina; Janssens, Nel (Routledge, 2017)
"This book offers perspectives on how to qualify and assess research in architecture, music and the arts. It creates a broader arena for discussion on doctorateness by establishing a framework for its application to creative fields. The book is grouped into three sections and includes contributions from international experts in the various fields working in Australia, Belgium, Brazil, Canada, Norway, Sweden, Switzerland, Spain, the Netherlands and the UK. The first section offers general frameworks for further conceptualising doctorateness in the fields in question. It is followed by a section that describes and discusses various experiences, concerns and visions on the production and assessment of doctoral research reporting from doctoral programmes in different stages of development. The third section includes future-oriented perspectives on knowledge-building processes, and asks how the ongoing, profound changes in academia could influence the concept of quality in both doctoral process and product."--